Classroom authority : theory, research, and practice - Pace, Judith L.; Hemmings, Annette B. (L. Erlbaum Associates, 2006)
Describes and analyzes authority relationships in classrooms through explorations of theory, prior research, and contemporary qualitative studies. This book is aimed at teacher educators, scholars, policymakers, students of education, and practitioners who seek empirically based understanding of authority.